2016
DOI: 10.3390/nu8090574
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns and Gestational Diabetes Mellitus in a Multi-Ethnic Asian Cohort: The GUSTO Study

Abstract: Gestational Diabetes Mellitus (GDM) is associated with an increased risk of perinatal morbidity and long term health issues for both the mother and offspring. Previous research has demonstrated associations between maternal diet and GDM development, but evidence in Asian populations is limited. The objective of our study was to examine the cross-sectional relationship between maternal dietary patterns during pregnancy and the risk of GDM in a multi-ethnic Asian cohort. Maternal diet was ascertained using 24-h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 42 publications
2
71
3
Order By: Relevance
“…However, sensitivity analyses in participants who completed a 3-d food diary produced similar estimates, albeit wider CIs (but not with abdominal adiposity measures, which might be due to the reduced sample size). In addition, we also showed that our 24-h recall is moderately valid and has good reproducibility in previously published results (27,29,30,52,62). Second, maternal diet was only assessed during 26-28 wk of gestation, which may not be representative of a diet followed throughout pregnancy.…”
Section: Discussionsupporting
confidence: 63%
“…However, sensitivity analyses in participants who completed a 3-d food diary produced similar estimates, albeit wider CIs (but not with abdominal adiposity measures, which might be due to the reduced sample size). In addition, we also showed that our 24-h recall is moderately valid and has good reproducibility in previously published results (27,29,30,52,62). Second, maternal diet was only assessed during 26-28 wk of gestation, which may not be representative of a diet followed throughout pregnancy.…”
Section: Discussionsupporting
confidence: 63%
“…Studies have been done in several countries to determine the prevalence of GDM in accordance with the new IADPSG criteria. The prevalence of GDM diagnosed by IADPSG criteria has been reported as 17.6%, 4.2%, 11.8%, 9.5%, 23.3%, 8.6%, and 45% in Singapore, Greenland, Switzerland, South Korea, Sri Lanka, Sub‐Saharan Africa, and the United Arab Emirates, respectively. By contrast, a two‐step approach for diagnosis determined a GDM prevalence of 3.3% in Switzerland and 12% in the United Arab Emirates .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined the association between dietary patterns during pregnancy and risk of GDM ( 17 21 ) . Results from these studies provided an evidence base for dietary recommendation to prevent GDM, but the findings were compromised by either relatively small sample size ( 17 , 18 ) or variance in study design ( 19 ) , dietary assessment tools ( 20 , 21 ) and diagnostic criteria for GDM ( 20 , 21 ) .…”
mentioning
confidence: 99%